Perception of Gen Z of Palembang City Towards Food Waste - Wulandari, Martha; Helmi, Sulaiman; Sartika, Dewi (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The problem of food waste has become a global issue that impacts economic, environmental, and social aspects. Indonesia is one of the countries with the highest levels of food waste, with around 41.4% of national waste in 2021 originating from food waste. In urban centers like Palembang, the rapid growth of population and urbanization contribute to increased food waste. Generation Z, representing about 24.34% of Indonesia's population, is identified as the age group that produces the most food waste. This research aims to explore the perceptions of Generation Z in Palembang City towards food waste, the factors influencing their behaviors, and the challenges they face. Using a descriptive quantitative method with purposive sampling, data were collected through online questionnaires and analyzed with descriptive statistics. The findings reveal that while Gen Z in Palembang is aware of the environmental and economic impacts of food waste, behavioral gaps persist due to impulsive buying, difficulties in portion estimation, and the influence of food delivery promotions. Efforts to reduce waste, such as proper food storage and reprocessing leftovers, have begun, but challenges persist. The study emphasizes the significance of targeted educational interventions, policy innovations, and community-based campaigns in promoting sustainable food consumption behaviors among Gen Z in Palembang